Sir Martin Frobisher seaman, soldier, explorer - Trow, Taliesin (Pen & Sword Maritime, 2010)
Taliesin Trow's new biographical study of this many-sided Elizabethan adventurer should revive interest in him and in this extraordinary period in English seafaring history. For Frobisher was a fascinating, enigmatic character whose reputation is often eclipsed by those of his remarkable contemporaries, Drake, Hawkins and Ralegh.